L’aggettivo vedico tra derivazione e lessico (ACME, 2020)
In some recent publications (Alfieri 2016, 2018, forth. a, b) a deep typological difference between the parts of speech system in Latin and in the Sanskrit language of the Rig-veda (RV) has been identified. In Latin, three major classes of simple morphemes are found (nouns, verbs and adjectives); in RV Sanskrit, only two major classes are found (nouns and verbal roots), and the most typical function of the “adjective” (i.e. the modifier that refers to a quality) is coded by a participial construction or a nominalization, that is to say by a derived nominal stem built on a verbal root meaning a quality. The present paper aims at re-examining the data discussed in those works to show that: a) the line that divides derivational morphology and the lexicon differs in Latin and in RV Sanskrit, since a whole part of speech (i.e. the adjective) is coded at the level of the lexicon in Latin, but at the level of word-formation in RV Sanskrit; b) the difference between Latin and RV Sanskrit depends on a typological change at the level of the parts of speech that was complete in Latin, but not yet in the RV (namely, the lexicalization of the former derived stems of Indo-European origin).